MRSA and Skin Infections in Psoriatic Patients: Therapeutic Options and New Perspectives - Giulio Rizzetto; Elisa Molinelli; Giulia Radi; Oscar Cirioni; Lucia Brescini; Andrea Giacometti; Annamaria Offidani; Oriana Simonetti (Antibiotics, 2022)
Psoriatic patients present various infectious risk factors, but there are few studies in the literature evaluating the actual impact of psoriasis in severe staphylococcal skin infections. Our narrative review of the literature suggests that psoriatic patients are at increased risk of both colonization and severe infection, during hospitalization, by S. aureus. The latter also appears to play a role in the pathogenesis of psoriasis through the production of exotoxins. Hospitalized psoriatic patients are also at increased risk of MRSA skin infections. For this reason, new molecules are needed that could both overcome bacterial resistance and inhibit exotoxin production. In our opinion, in the near future, topical quorum sensing inhibitors in combination with current anti-MRSA therapies will be able to overcome the increasing resistance and block exotoxin production. Supplementation with Vitamin E (VE) or derivatives could also enhance the effect of anti-MRSA antibiotics, considering that psoriatic patients with metabolic comorbidities show a low intake of VE and low serum levels, making VE supplementation an interesting new perspective.